MEMBANGUN KESADARAN HUKUM MASYARAKAT DESA UNTUK MEMBANGUN KELUARGA YANG BAHAGIA - Rasji,; Rahaditya,; Agung Valerama, (Jurnal Bakti Masyarakat Indonesia, 2022)
Indonesia has a population of 273.87 million, which places Indonesia as the country with the fourth largest population in the world. According to statistical data, the population of Indonesia who is married is 133.03 million jirwa and the divorced is 11.47%. Divorce shows the failure of a married couple in maintaining their marriage. This has an impact on the loss of happiness of the marriage partner and their offspring. Meanwhile the Marriage Law mandates that marriage is a physical and spiritual bond between a man and a woman to become husband and wife. The goal is for the married couple to become a happy and eternal family. This problem needs to be overcome by building legal awareness of marriage partners, so that marriage partners can build happy families. This problem has been given a solution through the implementation of community service activities (PKM). PKM is carried out using the method of lectures, guidance, and discussions between service providers and PKM partners. The devotee provided material related to marriage and efforts to build a happy family, which was followed by legal guidance, and interactive discussions with PKM partners. This activity has succeeded in equipping partners with an understanding of the law of marriage, the purpose of marriage, and how to overcome domestic problems, as well as building legal awareness of partners to maintain the integrity of their households and form a happy family forever. The implementation of PKM in Langut Village, Loh Beneficial District, Indramayu Regency has succeeded in instilling and increasing awareness of the village community about marriage law and the importance of building a happy family. The village community already has good knowledge of marriage law, has a good understanding of the legal aspects and benefits of marriage law, has a legal attitude in accordance with marriage law, and is able to behave legally according to marriage law. This awareness of the law of marriage is a provision for the village community to maintain the integrity of the household and build a happy family ABSTRAK: Indonesia memiliki penduduk sebanyak 273,87 juta jiwa, yang menempatkan Indonesia sebagai negara dengan jumlah penduduk terbanyak keempat di dunia. Menurut data statistik, penduduk Indonesia yang berstatus menikah sebanyak 133,03 juta jiwa dan yang bercerai sebanyak 11,47%. Perceraian menunjukan kegagalan pasangan suami istri dalam mempertahankan perkawinannya. Hal ini berdampak pada hilangnya kebahagian pasangan nikah beserta keturunannya. Sementara itu undang-undang perkawinan mengamanatkan bahwa perkawinan adalah ikatan lahir batin antara seorang pria dan wanita menjadi suami dan istri. Tujuannya adalah agar pasangan nikah tersebut menjadi keluarga yang bahagia dan kekal. Permasalahan ini perlu diatasi dengan membangun kesadaran hukum pasangan nikah, agar pasangan nikah mampu membangun keluarga yang bahagia. Permasalahan ini telah diberikan solusinya melalui pelaksanaan kegiatan pengabdian kepada masyarakat (PKM). PKM dilaksanakan dengan menggunakan metode ceramah, bimbingan, dan diskusi antara pengabdi dengan mitra PKM. Pengabdi memberikan materi yang berkaitan dengan perkawinan dan upaya membangun keluarga bahagia, yang dilanjutkan dengan bimbingan hukum, dan diskusi interaktif dengan mitra PKM. Kegiatan ini telah berhasil membekali pemahaman mitra tentang hukum perkawinan, tujuan perkawinan, dan cara mengatasi permasalahan rumah tangga, serta membangun kesadaran hukum mitra untuk mempertahankan keutuhan rumah tangganya dan membentuk keluarga yang bahagia selamanya. Pelaksanaan PKM di Desa Langut Kecamatan Lohbener Kabupaten Indramayu telah berhasil menanamkan dan meningkatkan kesadaran masyarakat desa tentang hukum perkawinan dan pentingnya membangun keluarga bahagia. Masyarakat desa telah memiliki pengetahuan hukum perkawinan yang baik, memiliki pemahaman aspek hukum dan manfaat hukum perkawinan dengan baik, memiliki sikap hukum sesuai dengan hukum perkawinan, serta mampu berperilaku hukum sesuai dengan hukum perkawinan